Design of high reliability power converters for aerospace applications - Harikumaran, Jayakrishnan (2022)
In this doctoral thesis, methods to design high reliability power converters for mission critical aerospace applications are studied. Aircraft platforms are increasingly being electrified necessitating usage of power converters for interfacing on-board sources and loads. Reliability of power converter systems is a key design requirement for future electric aircrafts. This thesis concentrates on predicting wear-out and cosmic ray induced random failures of drive converters. Various system voltage levels as well as two converter topologies are studied. The predicted reliability curves under a short haul aircraft mission profile are presented. It is shown that cosmic ray induced random failures dominate at higher system voltages in silicon IGBT based power converters. It is noted that SiC devices are a natural choice due to their resilience against cosmic ray failures. In order to address availability requirement due to the dominance of random failures, fault tolerance of multi three phase machines is presented. ABC domain model of a dual three phase machine is presented which can be extended to N three phase machines. The developed model can also represent fault states in the machine. The fault mode operation of dual three phase machine demonstrated a limp-home functionality by extracting torque from the damaged winding set under open phase faults. Even under dual open phase fault, approximately 25% torque can be realized using the fault tolerant controller. Furthermore, the controller architecture using PR controllers are easily reconfigurable with minimal modification enabling faster and straight forward validation of firmware for certification purposes.